A phase IV, two-armed, randomized, cross-over study comparing compliance with once-a-month administration of vitamin D3 to compliance with daily administration of a fixed-dose combination of vitamin D3 and calcium during two 6-month periods. Issue 12 (December 2015) - Bruyère, O.; Deroisy, R.; Dardenne, N.; Cavalier, E.; Coffiner, M.; Silva, S.; Niet, S.; Reginster, J.-Y.
Abstract Summary In a randomized, cross-over study, once monthly administration of vitamin D3 was preferred over a once daily administration of a fixed-dose combination of vitamin D3 and calcium, with a better compliance but without any significant difference in the increase in vitamin D levels. Introduction The aim of the present study was to compare a once-monthly administration of vitamin D3 to a daily administration of a fixed-dose combination of vitamin D3 and calcium during two treatment periods of 6 months. Methods One hundred volunteers aged 50 years old or older were randomized to receive either one drinkable ampoule containing 25, 000 IU vitamin D3 (D-Cure®, SMB) once monthly (group VD) or one chewable tablet containing 1000 mg calcium carbonate + 800 IU vitamin D3 (Steovit Forte®, Takeda) once daily (group VDCa) during 6 months. After the first 6 months of treatment, the groups were reversed according to the randomized cross-over design. Treatment compliance (i.e. the primary outcome), preference, acceptability and vitamin D levels and adverse events were all collected. Results For the two periods, the patients had a significantly higher compliance in the VD group than in the VDCa group (p < 0.0001). During the study, 50 (56.8 %) patients preferred the VD treatment, 16 (18.2 %) patients preferred the VDCa, and for 22 (25.0 %) patients, neither treatment was preferred. At the end of the first 6 months of treatment, the mean (SD) increase of 25(OH)D was 6.57 ng/mL (8.19) in the VD group and 3.88 ng/mL (10.0) in the VDCa group (p = 0.16 between groups). Conclusion In this study, a once-monthly administration of vitamin D3 was preferred over a once-daily administration of a fixed-dose combination of vitamin D3 and calcium, with a better compliance but without any significant difference in the increase in vitamin D levels.